2007
DOI: 10.1094/mpmi-20-12-1463
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Genes Encoded by the Supernumerary Chromosome Controlling AM-Toxin Biosynthesis and Pathogenicity in the Apple Pathotype of Alternaria alternata

Abstract: The apple pathotype of Alternaria alternata produces host-specific AM-toxin and causes Alternaria blotch of apple. Previously, we cloned two genes, AMT1 and AMT2, required for AM-toxin biosynthesis and found that these genes are encoded by small, supernumerary chromosomes of <1.8 Mb in the apple pathotype strains. Here, we performed expressed sequence tag analysis of the 1.4-Mb chromosome encoding AMT genes in strain IFO8984. A cDNA library was constructed using RNA from AM-toxin-producing cultures. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 53 publications
0
69
0
1
Order By: Relevance
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 88%
“…Host-selective toxin biosynthetic genes of A. alternata pathotypes appeared to be clustered on small chromosomes of Ͻ2.0 Mb in most of the strains tested (2,3,13,15,20,21,33,35). We demonstrated that small chromosomes that contain toxin biosynthetic genes from the strawberry, apple, and tomato pathotypes are conditionally dispensable (CD) chromosomes (2,15,21).…”
Section: Discussionmentioning
confidence: 88%
“…We have identified four genes, AMT1, AMT2, AMT3, and AMT4, involved in AM-toxin biosynthesis (Johnson et al 2000;Ito et al 2004;Harimoto et al 2007). AMT1 encodes a 479 kDa nonribosomal peptide synthetase containing four catalytic domains responsible for the activation of each residue in AM-toxin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1b) (Johnson et al 2000). AMT3 and AMT4 encode proteins with significant similarity to cytochrome P450 monooxygenases and thioesterase domains of nonribosomal peptide synthetase, respectively, from fungi (Harimoto et al 2007). In the apple pathotype strains, these genes were found to reside on small, conditionally dispensable (CD) chromosomes, which are not required for growth, but do confer an advantage for colonizing certain ecological niches (Covert 1998;Miao et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations